Influence and mechanism of resilience on flight operational performance under different flight situations: A study based on flight simulator experiments - Li, Li; Chen, Yao; Xing, Ruijie (Safety science, 2025)
•Three flight situations were simulated, including normal flight, single failure flight and multiple failures, the mental workload were measured.•Combining subjective weight and objective weight, a flight performance evaluation method under different flight situations was constructed.•The effects of resilience on flight performance under different flight situations were discussed.•The mediating effect of coping style on resilience and flight performance was discussed. To investigate the influence and mechanism of resilience on flight performance under different flight situations, an experimental platform was built based on the PI135 flight simulation equipment, and three different flight situations were designed, including normal flight, single failure flight, and multiple failures flight, with the approach and landing phase as the object of the study. 27 flight cadets, who had completed the simulation flight training course and passed the assessment, were recruited as subjects to conduct the experiment. The flight operation evaluation indexes were determined, the flight operation evaluation model was constructed. Mental workload and flight operation performance of different flight situations, resilience and coping styles of flight cadets’ were measured respectively. The results of the experimental data analysis showed that there were significant differences in flight performance under three different flight scenarios, and that flight operation performance decreased with increasing mental workload. Under three different flight situations, the flight operation performance of the high resilience group was significantly better than that of the low resilience group. Moreover, as the level of mental workload increased, the decline in flight operation performance for the low resilience group was greater than that of the high resilience group. Resilience did not have a significant effect on flight operation performance under normal flight situations but had a significant positive effect on flight operation performance under non-normal flight situations, especially under multiple failure flight situations where the effect of the toughness dimension of resilience was significant. The mediating effect test showed that positive coping styles had a partial mediating effect between resilience and flight operation performance under multiple failure flight situations, with a mediating effect of 39.96%, and the mediating effect of negative coping styles was not significant.